Economic Development and Fiscal Policy in CO2 Emission Mitigation: A Dynamic Panel Study in Indonesia Before Covid 19 - Agus Tri Basuki (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the impact of economic development and fiscal policy on CO2 emissions in Indonesia. Using a time series data from 2009 to 2019 covering 20 provinces in Indonesia before the COVID-19 pandemic, this study analyzed data with a dynamic panel approach. The results show that in the short term, Gross Regional Domestic Product (GDP) and population have a negative influence on CO2 emissions, while in the long term, GDP and population have a positive effect on CO2 emissions. The Central to Regional Transfer Fund (DAU) shows a positive effect on CO2 emissions in the short term but has a negative effect in the long term. Spending on education has a negative effect on CO2 emissions in the short term, while in the long term, it has no significant effect. Spending on health has shown no effect on CO2 emissions in either the short or long term. Foreign Direct Investment (FDI) has a negative effect on CO2 emissions in both periods. Based on these findings, the policy that needs to be considered in the future is to strengthen the policy of transferring Central Transfer Funds to Regions that better supports environmentally friendly initiatives, as well as encourage foreign investment oriented towards green and sustainable technology. In addition, the allocation of funds for the education sector can be prioritized for the development of policies that support the reduction of CO2 emissions, while health spending can be directed to programs that integrate economic growth with environmental sustainability.